Golden Gate International Exposition on Treasure Island, San Francisco (Stanley A. Plitz Company)
Golden Gate International Exposition is situated in the center of San Francisco Bay on Treasure Island and occupies a most unique and picturesque setting. On a Magic Isle, a World's Fair has been built to celebrate the completion of the World's largest Bridge. An auto trip over the World's largest Bridge either from the East Bay shore or San Francisco, alone gives a thrill. Large ferries also operate from either shore. Thus, in ten minutes or less you arrive at this Isle of the Pacific beauty and view a new horizon of glory and splendor. February 18th to December 2nd 1939.